Female song rates in response to simulated intruder are positively related to reproductive success - Cain, Kristal E.; Cockburn, Andrew; Langmore, Naomi E. (Frontiers in Ecology and Evolution, 2015)
Bird song is well studied in males as a sexually selected behavior. However, although song is also common among females, it is infrequently examined and poorly understood. Research suggests that song is often used as a resource defense behavior and is important in female-female competition for limited resources, e.g. mates and territories. If so, song should be positively related to fitness and related to other resource defense behaviors, but this possibility has rarely been explored. Here we examine fitness estimates in relation to spontaneous song rates and song rates in response to a simulated intruder (playback), in the superb fairy-wren (Malurus cyaneus), a cooperatively breeding songbird. We also determine how song rates relate to other territorial defense behaviors. Song rate in response to playback, but not spontaneous song rate, was positively related to nest success and the number of fledglings produced by successful females. Further, response song rate was also correlated with other territorial defense behaviors (latency to respond and flights). This evidence supports the hypothesis that female song may be used in the context of female-female competition to improve access to limited reproductive resources, and suggests that song may provide direct fitness benefits.